SIRI Mathematical Modeling on the Spread of Typhoid Disease in South Sulawesi and Batik Motifs from the Simulation - Najib, Muhammad; Jannah, Irodatul; Maharani, Aurora Sylvia; Sugiyanto, Sugiyanto (Proceeding International Conference on Religion, Science and Education, 2026)
Typhoid disease is one of the significant public health problems in Indonesia, especially in the South Sulawesi region. In an effort to understand and control the spread of this disease, the mathematical modeling of SIRI (Susceptible, Infected, Recovered, and Immune) can be used as an effective analysis tool. This journal aims to explore the dynamics of the spread of typhoid disease in South Sulawesi by using the SIRI model, as well as connecting it with batik motifs inspired by the patterns of the spread of the disease. Through the simulation carried out, the modeling results show that factors such as population density, sanitation, and community behavior play an important role in determining the rate of spread of typhus. Statistical data from the Health Office shows that the incidence of typhus in South Sulawesi has experienced significant fluctuations, with the peak incidence in certain months related to the rainy season. In addition, the batik motif produced from the results of this simulation reflects the complexity and beauty of the disease spread pattern, which can be used as an educational medium to increase public awareness about the importance of disease prevention. Thus, this journal not only provides insight into the spread of typhus, but also invites the public to better understand and appreciate local culture through batik art.